Heritage, world heritage, and the future (İstanbul)
[3], 296 sayfa
Keywords: “The papers published in this volume were among those presented at the 14th International ANAMED Annual Symposium (IAAS), held at Istanbul’s Koç University Research Center for Anatolian Civilizations in 2019. Bringing together archaeologists and heritage professionals from diverse backgrounds engaged in the conservation of archaeological and natural sites, the symposium focused on topics of heritage conservation and development in Turkey, with a particular focus on World Heritage Sites. The papers in this volume explore the conservation and future of archaeological and natural heritage, including but not limited to the World Heritage Convention and its application in Turkey, site conservation and financing of conservation work, community engagement during archaeological research, and public perceptions of archaeology. Providing reflection on and critical assessment of their own work, the authors discuss both achievements and problems to create a clearer picture of what works and what does not work in certain conditions“ -- Yayıncı.